POTENSI LUMPUR SAWIT/PALM OIL SLUDGE (POS) SEBAGAI PAKAN SAPI POTONG DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Junaidi dan; Dewi Febrina (Jurnal Peternakan, 2008)
The objective of this study was to know potencial of solid waste in Bagan Sinembah, Rokan Hilir distric, Riau. Research carried out at December 2007 in Bagan Sinembah, by using three factories of Elaeis guineensis (PKS). The three factories were used from data collection were PT. Sinar Perdana Caraka (SPC), PT. Dharma Wungu Guna (DWG), and Pr. Geliga Bagan Riau (GBR). The results of study indicate that solid waste in Bagan Sinembah, Rokan Hilir district, Riau Province had a great potencial. Productions of solid waste in Bagan Sinembah was around 25.360,20 tons/year and carrying capacity 3.474 Animals Unit. Farmers will use solid waste at large quantity if they raised livestock in commercially, for instance for fattening purpose. The strategies which can be applied to maximize solid waste utilization is through partnership between farmers and factories or local goverriment